REKAYASA MESIN PENGERING PADI BAHAN BAKAR SEKAM (BBS) KAPASITAS 10 T TERINTEGRASI UNTUK MENINGKATKAN NILAI EKONOMI PENGGILINGAN PADI DI LAHAN PASANG SURUT SUMATERA SELATAN - Sutrisno, Sutrisno; Raharjo, Budi (Publikasi Penelitian Terapan dan Kebijakan, 2008)
Research about designing and building a 10 t capacity husk paddy dryer which integrated in rice milling in tidal swampy area in South Sumatera have done at 2007. Thi addres of research place is Telangrejo village, channel 8, bridge 5. This research was done by unity system that invide many institutions and every institution have give contribution to the research. They are : BPTP Sout Sumatera as field coordinator, SSFFMP of Urope Union in Palembang have contributed a Vietnam model of axial blower with 76 cm diameter and decimination activity, the RMU owner in Telangrejo village (private party) have contribute drying chamber made by cocrate with 10 t capacity, and a building where the husk dryer builded, BBPMP Serpong was funded this rearch, and supervisor, and BB Padi was contributed uniit husk furnace with 10 t capacity, diesel engine â€œYanmarâ€ with 23 HP, and another any things that needed to finishing this reseach. After the building of husk dryer have been finished, the next activity is testing the dryer The testing consist with functionally and verification testing . The results of the functionally testing was shown that all components of the dryer are have good performens for 10 t capacity. The paddy quality which used for testing was low. The water content was hight, 27.50 % and the green kernel was hightly also. The results of testing showed that for reduced water content from 27.50 % to 14.10 % needed time 12 hours. The velocity of drying air through out the paddy bulk in the drying chamber was 7.00 m/minute.The drying process happen with average of drying air temperature was 42 Â°C. Results of milling test showed that the rice recovery of paddy that dryed by machine and sun drying were 65 % and 62 % respectively. The percentage of head rice was 74.54 % and 44.30 % respectively, and the rice price were Rp5,000 and Rp4,500 respectivelly.Based on to the economic calculation showed that using of 10 t box dryer energy dryer, can resulted added value Rp 5,194,000.- per operation, higher then using 6 t and 3 t capacities that resulted added value Rp 2,457,660.- and Rp 1,0228,830.- respectivally.